Effect of Dietary Amorphophallus sp From East Java on LDL-C Rats (Rattus novergicus Wistar Strain) - Nunung Harijati; Sri Widyarti; Rodiyati Azrianingsih (Journal of Tropical Life Science, 2011)
One of indication of obesity is high LDL-C . Obesity has serious risk to health, it can cause heart disease and stroke. Effort to lower obesity using drugs have significant side effects such as insomnia, increased blood pressure, dry mouth and so forth. Therefore using natural products that contain glucomannan to reduce obesity and LDL-C is good choise. Glucomannan in the global market derived from Amorphophallus konjac. In this study, we used glucomannan from Amorphophallus endemic East Java to reduce fattened Wistar rats. Amorphophallus that used include Amorphophallus muelleri, A.variabilis (variant: Brongkos 32; Brongkos 5; Wonorejo, Brangsi) and Amorphophallus campanulatus (Var Selopuro). Amorphophallus diet was given to white rats of Wistar strain that previously fattened using a mixture of cholesterol and lard, in addition to PARS (Chicken Feed Race Super) as a basic food. Amorphophallus konjac was used as control. Measurement of LDL-C was conducted in four different time points, namely 1). Prior to dietary cholesterol, 2). 24 days after the dietary cholesterol, 3) 11 days after Amorphophallus (+cholesterol) diet, 4). 25 days after Amorphophallus (+cholesterol) diet. The results showed that the diet of A.variabilis potentially lowered blood cholesterol levels for their respective 22.98%, 5.85% and 7.37% for consecutive variant Brongkos 32; Brongkos 5; Wonorejo. Diet from A.campanulatus and A.konjac had not been able to reduce cholesterol to the end of observation (25 days).Keywords: LDL-C, A.variabilis, A.muelleri, A.campanulatus, A.konjac